2019
DOI: 10.1097/cmr.0000000000000572
|View full text |Cite
|
Sign up to set email alerts
|

Immunotargeted therapy in melanoma: patient, provider preferences, and willingness to pay at an academic cancer center

Abstract: New melanoma therapies have shifted the expectations of patients and providers. Evaluating the impact of treatment characteristics may enhance shared decision making. A survey, including a discrete choice experiment, was utilized to evaluate perceived trade-offs of different melanoma treatments and to estimate out-of-pocket (OOP) willingness-to-pay (WTP) thresholds (January 2016 to March 2016). Participants included patients with melanoma at Huntsman Cancer Institute and their cancer care providers. Stakeholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 23 publications
2
23
0
6
Order By: Relevance
“…Hence, the risks and benefits vary considerably between the possible treatment options [ 10 , 11 ]. In a recent study on treatment choices, melanoma patients (stages I–IV) and their providers systematically accepted all levels of risk for adverse events in exchange for improved survival rates [ 12 ]. This finding suggests that patients make extreme, yet conscious, decisions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the risks and benefits vary considerably between the possible treatment options [ 10 , 11 ]. In a recent study on treatment choices, melanoma patients (stages I–IV) and their providers systematically accepted all levels of risk for adverse events in exchange for improved survival rates [ 12 ]. This finding suggests that patients make extreme, yet conscious, decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Targeted therapy has a higher response rate but does not offer a long-term benefit comparable to that of checkpoint inhibitors, due to the mechanisms of resistance. As the overall survival rate is the strongest determinant of the treatment decision, patients with melanoma (stages I–IV) and their providers systematically prefer combination immunotherapy over targeted therapy [ 12 ]. However, in some clinical situations, e.g., in symptomatic patients, the need for tumor reduction might lead to a recommendation of BRAF/MEK inhibition therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A DCE by Stenehjem and colleagues revealed that melanoma patients and care providers had the highest preference for OS and avoidance of immunotherapy‐related AE, even though the perceptions about quality of life expectations and PFS differed [26]. Both patients and care providers reported higher WTP for ipilimumab plus nivolumab than for BRAF/MEK inhibitors [26]. According to a DCE by Mansfield et al., melanoma patients were willing to trade an increased risk of AE for prolonged PFS [27].…”
Section: Introductionmentioning
confidence: 99%
“…We recently conducted a DCE on preferences for key attributes of modern systemic melanoma treatments of patients with advanced melanoma (AJCC stage IIC–IV) from five German skin cancer clinics [29]. Concordant with the industry‐sponsored studies mentioned above [24–27], our participants had highest preferences for efficacy, followed by safety, but preferences varied significantly depending on age, marital status, education and treatment experience [29].…”
Section: Introductionmentioning
confidence: 99%